2020
DOI: 10.3390/pharmaceutics12080774
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Histidine-Based Carriers for Nucleic Acid Delivery: Advances and Challenges

Abstract: Histidines incorporated into carriers of nucleic acids may enhance the extracellular stability of the nanoparticle, yet aid in the intracellular disruption of the nanoparticle, enabling the release of the nucleic acid. Moreover, protonation of histidines in the endosomes may result in endosomal swelling with subsequent lysis. These properties of histidine are based on its five-member imidazole ring in which the two nitrogen atoms may form hydrogen bonds or act as a base in acidic environments. A wide variety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 115 publications
1
30
0
Order By: Relevance
“…First, the buffering capacity of a polymer at acidic pH has been found to be a significant factor in its efficacy as a delivery vehicle. 88,90 Certain moieties, such as imidazole 91,92 and guanidine 93,94 groups, have been found to be particularly effective at facilitating complexation and endosomal escape. Bisphenol-A (BPA)-containing groups have also been found to be effective when incorporated into PBAEs; 86,95 interestingly, BPA-derived compounds may also improve efficacy when added as excipients to other NPs.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…First, the buffering capacity of a polymer at acidic pH has been found to be a significant factor in its efficacy as a delivery vehicle. 88,90 Certain moieties, such as imidazole 91,92 and guanidine 93,94 groups, have been found to be particularly effective at facilitating complexation and endosomal escape. Bisphenol-A (BPA)-containing groups have also been found to be effective when incorporated into PBAEs; 86,95 interestingly, BPA-derived compounds may also improve efficacy when added as excipients to other NPs.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…The mPEG-b-P(MAAc-g-His)-NH 2 copolymers can be absorbed on and shield the positive charges of cationic liposomes through electrostatic interactions for fabricating pH-sensitive charge-conversion polymer–liposome complexes at neutral pH and to desorb from cationic liposomes via charged neutralization at low pH ( Figure 1 ). In addition, because histidine molecules caused the proton sponge effect at low pH [ 24 ], copolymers could induce CTPP-containing cationic liposomes escaping out of the endosomes to target and deliver the payload to mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…Imidazoles carry pKa values around 5.0–6.5 and thus can protonate to assume a positive charge in response to weakly acidic pH in pathophysiological settings [ 21 ]. The incorporation of imidazole-based lipids into nano-formulations has enhanced their intracellular delivery of proteins and nucleic acids [ 22 , 23 ]. However, very few studies [ 24 ] have been reported on imidazole-based nano-formulations for anticancer drug delivery.…”
Section: Introductionmentioning
confidence: 99%